Diplomasi Peace Corps: Bantuan Sukarelawan Amerika Syarikat di Malaysia, 1961 – 1983 - Bilcher Bala (2018)
In 1961, the United States government had established a Peace Corps agency as a volunteer assistance program to Third World countries. Peace Corps volunteers play an important role in diplomacy by building closer social ties with locals besides providing aid in terms of technical skills in the field of education, health, community development, and agriculture. Malaysia is one of the first countries to receive the Peace Corps assistance in 1962. This article focuses on the existence of bilateral diplomacy between the United States and Malaysia, the concept of Peace Corps diplomacy, and the development of its program in Malaysia until the termination in 1983.